Antiradical activity and phenolic constituents of Stachys milanii aerial flowering parts methanol extract - Kukić-Marković, Jelena; Milutinović, Violeta; Niketić, Marjan; Petrović, Silvana (Archives of Pharmacy, 2022)
Stachys milanii Petrović (Lamiaceae) is an endemic of central and eastern part of Balkan Peninsula, growing mainly in river valleys on semi-saline soils, often along the edge of cereal fields and abandoned arable lands. It is a critically endangered and strictly protected species in Serbia, with just one proven habitat. So far it was investigated on herb essential oil composition and antimicrobial activity, and on fatty acid composition of seeds. Aim of this work was to investigate antiradical potential and phenolic constituents of dry methanol herb extract. Aerial flowering parts (herb) of S. milanii were collected in North Macedonia (Ovče Pole). Powdered, dried plant material was extracted by bimaceration with chloroform, and then with methanol. Obtained dry methanol extract was used for further analysis. Using appropriate spectrophotometric procedure strong, concentration-dependant anti-DPPH activity of extract was observed (SC50=34.15 μg/mL). Also spectrophotometrically, using Folin-Ciocalteu reagent, significant total phenolics content (0,47 mg gallic acid/mg dry extract) was determined. In TLC-DPPH test observed yellow zones indicated presence of few compounds which strongly neutralized purple DPPH radical. LC-MS analysis revealed presence of one phenolic acid, four phenylethanol glycosides, eight flavonoid glycosides derivatives of 8-hydroxyflavones, and one apigenin glycoside. Using commercial standards in extract were identified and quantified: chlorogenic acid (1.63%) and acteoside (2.65%), as the main phenylethanoid. In 8-hydroxyflavones fraction six hypolaetine and two isoscutellarein derivatives were present; using compounds previously isolated from S. alpina subsp. dinarica Murb. herb, 4’-O-methylhypolaetine-7-O-[6’’’-acetylallosyl(1®2)]-glucopyranoside and isoscutellarein-7-O-[6’’’-acetylallosyl(1®2)]-glucopyranoside were identified, representing the most prominent flavonoids in investigated extract, respectively.